Peronism, university and reformist opposition. The case of la plata city/ciudad eva perón (1943-1955) (Estudios Sociales, 2018)
In this work, we present a reconstruction of the conflicts and transformations that the National University of La Plata ( UNLP ) experienced during the peronist decade, considering both the official voice (the projects of peronist managements) and the opposition (the action of reformism). First, we will investigate the transformations that the UNLP went through between 1943 and 1955. Secondly, we are going to analyze the opposition actions that the reformist youths grouped in the University Federation of La Plata carried out.
Keywords: University; peronismo; students; university reformism; La Plata